2020
DOI: 10.1002/rmb2.12323
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects mitochondrial quantity by activating SIRT1/PGC‐1α expression during ovarian hypoxia

Abstract: Purpose Resveratrol is a well‐known potent activator of sirtuin‐1 (SIRT1). We investigated the direct effects of hypoxia and resveratrol on SIRT1/ peroxisome proliferator‐activated receptor‐gamma coactivator 1α (PGC‐1α) pathways, vascular endothelial growth factor (VEGF), hypoxia‐inducible factor (HIF)‐1α, and mitochondrial quantity in a steroidogenic human ovarian granulosa‐like tumor cell line (KGN) cells. Methods KGN cells were cultured with cobalt chloride (CoCl2; a hypoxia‐mimicking agent) and/or resverat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Several studies have confirmed that some drug-resistant tumor cells are particularly strongly dependent on PGC-1α-mediated metabolic activity, and the inhibition of PGC-1α expression sensitizes some tumor cells to treatment, including lung cancer cells ( 153 ). The expression of a subset of known PGC-1α-regulated genes appears to be altered indirectly by changing the metabolic state of cells exposed to hypoxia and nutrient deprivation ( 154 ). Interestingly, PGC-1α is a regulator of PPAR-γ activity, and the dysregulated expression of PGC-1α may affect PPAR-γ function.…”
Section: Pgc-1α/ppar-γ Signaling In Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that some drug-resistant tumor cells are particularly strongly dependent on PGC-1α-mediated metabolic activity, and the inhibition of PGC-1α expression sensitizes some tumor cells to treatment, including lung cancer cells ( 153 ). The expression of a subset of known PGC-1α-regulated genes appears to be altered indirectly by changing the metabolic state of cells exposed to hypoxia and nutrient deprivation ( 154 ). Interestingly, PGC-1α is a regulator of PPAR-γ activity, and the dysregulated expression of PGC-1α may affect PPAR-γ function.…”
Section: Pgc-1α/ppar-γ Signaling In Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…In response to hypoxic conditions, the posttranslational regulation of molecular mediators such as SIRT1, HIF-1α, PGC-1α, and AMPK may play a critical role in the control of the glycolytic-mitochondrial energy axis ( Figure 3 ) ( 171 , 173 ). SIRT1 and PGC-1α are supposed to exist in the mitochondria of tumorigenesis, where they function as critical inducible factors for intercellular energy metabolism and gene regulation ( 154 , 174 ). SIRT1 is known to promote mitochondrial biogenesis.…”
Section: Sirt1/pgc-1α/ppar-γ In Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…Formation of the antrum then appears to reduce oxygen demands (as the fluid compartment does not consume oxygen) and facilitate oxygen diffusion towards the oocyte (Redding et al, 2007). Granulosa cells also adapt their oxygen consumption during antral follicle growth in order to leave an optimal oxygen supply for the oocyte (Li et al, 2013) by upregulating the hypoxia-inducible factor 1 (HIF1) signaling pathway during their rapid growth (Harris et al, 2007;Kind et al, 2015;Nishigaki et al, 2020;Zhou et al, 2018;). HIF1 is one of the master regulators of response to hypoxia (Takahashi et al, 2016;Zhou et al, 2018).…”
Section: Hypoxia In the Ovarymentioning
confidence: 99%
“…During follicle growth, increased VEGF expression not only has a proangiogenic function, carrying blood around follicles, but also plays a role in signaling involved in granulosa cell proliferation (Nishigaki et al, 2020;Yalu et al, 2015). In fact, VEGF is one of the main regulators of granulosa cell proliferation in hypoxic conditions through the PI3K/Akt signaling pathway, with a subsequent upturn in expression of one of its main effectors, mammalian target of rapamycin (mTOR) (Shiratzuki et al, 2016).…”
Section: Hypoxia In the Ovarymentioning
confidence: 99%
“…Remarkably, the mitochondrially-targeted Mito-Q has been demonstrated to protect the intestinal barrier by ameliorating mitochondrial DNA damage via the Nrf2/ARE signaling pathway [238]. Resveratrol can restore the suppressed SIRT1 expression and mtDNA expression in a cellular model of ovarian hypoxia [239]. Flavanones (in particular, naringin) are able to modulate mtDNA copy number in human leukocytes and has been identified as the key factor behind the association between fruit consumption and mtDNA copy number measured in a population based study [240].…”
Section: Antioxidants and Mitochondria: From The General Function To mentioning
confidence: 99%